The Position of Siri's Husband Regarding the Distribution of Inheritance Assets in the Case at the Enrekang Religious Court from an Islamic Legal Perspective (Determination Study Number 161/PDT.P/2022/PA EK) - Abd Jamil Salam; Rusdaya Basri; M. Ali Rusdi; Aris; Saidah (Universitas Muhammadiyah Palu, 2025)
The main problems in this research are 1) What are the Judge's Legal Considerations in Decision Number 161/Pdt.P/2022/Pa Ek?. 2) What is the Position of Siri's Husband as the Heir of Siri's Wife from a National Law Perspective? 3) What is the Position of Siri's Husband? As the Heir of Siri's Wife Seen from the Perspective of Islamic Law? This research uses a type of library research with a normative juridical approach. Data collection techniques using document studies (library materials). The theories used are utility theory and legal certainty theory. The results of the research concluded that 1) The judge's legal considerations in Judge Determination Number 161/Pdt.P/2022/Pa Ek were that the panel of judges did not include the husband of the deceased as an heir because there was no clarity regarding the condition of the deceased's husband. And there is no legally registered marriage registration. Therefore, the heirs from the unregistered marriage only fell to the deceased's biological mother and her 2 children. 2) The position of the unregistered husband as the legal representative of the unregistered wife, viewed from the perspective of national law, is that in an unregistered marriage there is no distribution of assets to the wife or children resulting from an unregistered marriage, unless there is an agreement or civil agreement between the husband and wife only. The existence of an agreement in a deed made before a Notary opens up opportunities for wives and children resulting from unregistered marriages to receive a share of the mutually beneficial assets. An unmarried wife/husband can obtain mutually beneficial assets through a mediation or negotiation process between husband and wife, with the help of a legal consultant or the family. 3) The position of the unregistered husband as the wawris expert of the unregistered wife is viewed from the perspective of Islamic law. In this case it can be said that a marriage that does not meet the provisions of maqashid sharia is considered not in accordance with the purpose of the marriage itself so that the marriage is not fulfilled.